Rel B‐modified dendritic cells possess tolerogenic phenotype and functions on lupus splenic lymphocytes in vitro. Issue 1 (September 2016) - Wu, Haijing; Lo, Yi; Chan, Albert; Law, Ka Sin; Mok, Mo Yin
Summary: Systemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by high morbidity and mortality and its treatment remains challenging. Dendritic cells (DCs) have been shown to participate in the initiation and perpetuation of lupus pathogenesis and the DCs that can induce tolerogenicity appear as potential cell‐based therapy in this condition. In this study, we examined the in vitro tolerogenic properties of bone‐marrow derived DCs (BMDCs) in the murine lupus setting. We used lentiviral transduction of RelB‐silencing short hairpin RNA to modify the expression of RelB, a key transcription factor regulating DC maturation, in BMDCs from MRL/MpJ mice. Tolerogenic properties of RelB‐modified DCs were compared with scrambled control (SC) ‐modified DCs. RelB expression was found to be significantly reduced in RelB‐modified DCs derived from MRL/MpJ mice, wild‐type of the same genetic background as MRL/lpr lupus‐prone mice. These MRL/MpJ RelB‐modified DCs displayed semi‐mature phenotype with expression of lower levels of co‐stimulatory molecules compared with SC‐modified DCs. RelB‐modified DCs were found to be low producers of interleukin‐12p70 (IL‐12p70) and could induce hyporesponsiveness of splenic T cells from MRL/MpJ and MRL/lpr mice. Furthermore, they down‐regulated interferon‐ γ expression and induced IL‐10‐producing T cells in MRL/MpJ splenocytes, and attenuated interferon‐ γ and IL‐17 expression in MRL/lpr splenic CD4 + lymphocytes. Splenocytes primed by RelB‐modified DCs demonstrated antigen‐specific suppressive effects on allogeneic splenocytes. In conclusion, RelB‐silencing in DCs generates DCs of tolerogenic properties with immunomodulatory function and appears as potential option of cell‐targeted therapy. Abstract : Lentiviral transduction of RelB‐silencing short hairpin RNA to modify RelB expression in bone‐marrow‐derived dendritic cells (BMDCs) can lead to acquisition of tolerogenic properties. These BMDCs were shown to have a stable semi‐mature phenotype with low co‐stimulatory molecule expression. They can also induce hyporesponsiveness of allogeneic T cells, attenuate interferon‐γ and interleukin‐17 expression of T cells and induce T cells with antigen‐specific suppressive function.